An Improved Load Balancing in MANET Using on-Demand Multipath Routing Protocol - Yamsani, Nagendar; Kumar, Bura Vijay; Aluvala, Srinivas; Dandugudum, Mahesh; Reddy, G. Sunil (International Journal of Engineering and Technology, 2018)
In this fast growing application usage towards the wireless communication led to concentrate on the mobile ad-hoc networks (MANETs) in most parts of the globe. Although MANETs are widely used in many of the commercial, military and medical applications, they are inflexible with the traffic congestion route failure, delay, and throughput results in the performance degradation. As there several routing protocols that mainly relies on the shortest route to the destination, usage of less hop count, but none of them proved to complete solution to the multipath routing in case of load balancing in the network. So in this paper we try to put our efforts to apply an efficient load balancing Ad-hoc On-demand Multipath Distance Vector (LBA-AOMDV) that have the ability to maintain constant load among the nodes by balancing the traffic among the multipath routes whenever required. To show the performance of the algorithm in terms of its performance metrics such as throughput, delay and packet loss from the source to destination for the nodes, the total simulations are carried on the NS-2.32 tool.